(untitled) (Current Horticulture, 2024)
The differential expression pattern of molecular chaperones genes was studied in developing storage and fibrous root tissues of sweet potato [Ipomoea batatas (L.) Lam.] using hybridization array. Out of 121 chaperone genes, 76 and 45 genes displayed more than 1.5-fold induced and reduced expression, respectively during the initial storage root development as compared to the non-tuber forming fibrous root of sweet potato. The differentially expressed genes belong to different chaperone family included DNAJ, HSP90, HSP100/ClpATPase, HSP20, families etc. These differentially expressed chaperones are known to play an important role in hormone signalling, nucleosome remodelling, protein import, protein folding and proteasomal degradation. Thus, our study shows the functional role of molecular chaperones in development of storage-roots of sweet potato, providing further scope for chaperone mediated functional genomics studies and CRISPER-mediated breeding of storage root development in sweet potato.